Resurrection - Tolstoy, Leo, graf, 1828-1910 (Everyman's library, 2025)
"A beautiful hardcover edition of Tolstoy's most controversial novel: the dramatic tale of a remorseful nobleman who seeks redemption after a woman he once wronged is convicted of murder--only to discover a whole world of injustice previously unknown to him. Called to serve on the jury of a murder trial, Prince Dmitry Nekhlyudov is devastated to recognize the defendant, Katerina, as a young woman he had seduced and abandoned years before. Pregnant with his child, she was cast out of her home and had turned to prostitution to survive, only to be charged with poisoning a client who beat her. Struck by the tragic consequences of his selfish actions, Dmitry decides to give up his life of wealth and privilege to devote himself to rescuing Katerina, even if it means following her into exile in Siberia. With its colorful cast of characters that range from peasants to aristocrats, and from bureaucrats to convicts, Tolstoy's novel, first published in 1899, creates a vivid panorama of Russian life. Everyman's Library pursues the highest production standards, printing on acid-free cream-colored paper, with full-cloth cases with two-color foil stamping, decorative endpapers, silk ribbon markers, European-style half-round spines, and a full-color illustrated jacket. Everyman's Library Classics include an introduction, a bibliography, and a chronology of the author's life and times."